2022
DOI: 10.1186/s13075-022-02983-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of the sirtuin family in cartilage and osteoarthritis: molecular mechanisms and therapeutic targets

Abstract: Osteoarthritis (OA) is mainly characterized by the progressive destruction of articular cartilage. Mounting studies have revealed that disruption of extracellular matrix (ECM) homeostasis, aberrant chondrocyte metabolism, an increase in the number of senescent chondrocytes and abnormal activation of cell death such as chondrocyte apoptosis and autophagy, are the crucial steps in OA development. Additionally, mitochondrial dysfunction also participates in the abovementioned processes and is the key element of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…They are essential in terms of cellular anti-aging mechanisms, by being involved in DNA repair, antioxidative defense regulation, and immunomodulation. Therefore, sirtuins are considered to be important targets to counteract age-related diseases, including OA and OP [ 21 , 22 ]. Indeed, sirtuins have been found to maintain tissue anabolism, prevent apoptotic cell death, and attenuate senescence and inflammation in cartilage [ 23 27 ] as well as in bone [ 28 , 29 ].…”
Section: The Cellular Antioxidant Defense Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…They are essential in terms of cellular anti-aging mechanisms, by being involved in DNA repair, antioxidative defense regulation, and immunomodulation. Therefore, sirtuins are considered to be important targets to counteract age-related diseases, including OA and OP [ 21 , 22 ]. Indeed, sirtuins have been found to maintain tissue anabolism, prevent apoptotic cell death, and attenuate senescence and inflammation in cartilage [ 23 27 ] as well as in bone [ 28 , 29 ].…”
Section: The Cellular Antioxidant Defense Systemmentioning
confidence: 99%
“…Furthermore, recent studies demonstrated that Sirt1 and Sirt6 are downregulated in senescent chondrocytes. While Sirt1 suppresses the expression of SASP factors, Sirt6 presumably promotes DNA repair [ 219 ]. Accordingly, increased Sirt1 and Sirt6 expression attenuates OA progression by diminishing chondrocyte senescence [ 220 222 ].…”
Section: Ros-mediated Cell Fate Decision In Oamentioning
confidence: 99%
“…Although human chondrocytes from osteoarthritis cartilage samples, human knee articular chondrocytes [ 63 , 64 ], and chondrosarcoma HTB-94 cells express SIRT1 [ 64 ], their expression decreases with age, contributing to a higher risk of osteoarthritis development in humans and mice [ 64 , 65 ]; this is due to a shift in chondrocyte activity toward catabolic proteolysis, increasing the rate of apoptosis, together with lower chondrogenic action [ 64 ], decreasing autophagy, and accelerating chondrocyte senescence [ 66 ]. However, the exact mechanism of SIRT1 activation in chondrocytes and its role in age-associated osteoarthritis are poorly understood.…”
Section: The Importance Of Estradiol–sirtuin-1 Signaling In the Physi...mentioning
confidence: 99%
“…It has been reported that OA affects about 12% of elderly individuals, 2 and its incidence is increasing around the world 3 . Abnormal chondrocyte apoptosis and defect in extracellular matrix (ECM) homeostasis have been recognized to participate in OA pathogenesis 4 . Currently, the therapeutic approaches for OA are conservative treatments, including pain relief and anti‐inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…3 Abnormal chondrocyte apoptosis and defect in extracellular matrix (ECM) homeostasis have been recognized to participate in OA pathogenesis. 4 Currently, the therapeutic approaches for OA are conservative treatments, including pain relief and anti-inflammatory drugs. So far, there is still lack of disease-modifying treatments for OA.…”
mentioning
confidence: 99%